In-situ TEM investigation of dislocation loop reaction and irradiation hardening in H2+-He+ dual-beam irradiated Mo. (30th April 2022) - Li, Yipeng; Ran, Guang; Liu, Xinyi; Han, Qing; Huang, Xiuyin; Ding, Yifan
Highlights: Irradiation can directly cause the formation of 1/2<111> loops and <100> loops. Irradiation can directly induce 1/2<111>loop to transform into <100> loop. Two 1/2<111> loops react to form <100> loop without strict size similarity condition. Yield strength increment caused by irradiation-induced loops is analyzed. Loop evolution and its relationship with irradiation dose are established. Abstract: Through in-situ TEM observation during 30 keV H2 + -He + dual-beam irradiation at 723 K, the reaction and transformation of dislocation loops in pure Mo were investigated, especially for <100> loops. Irradiation could directly cause the formation of 1/2<111> loops and <100> loops, but 1/2<111> loops were dominant. In-situ observation confirmed the formation mechanism of <100> loops, including direct irradiation induced mechanism, 1/2<111> loop direct conversion mechanism, and reaction mechanism of two 1/2<111> loops. Meanwhile, the reaction of two 1/2<111> loops to produce <100> loop should not require the strict size similarity condition. The reaction between 1/2<111> loops could also produce 1/2<111> loop, which was essentially a process in which one loop absorbed another one. The yield strength increment caused by irradiation-induced loops was analyzed, and its saturation value reached 0.48 GPa at 0.06 dpa. Compared with single He + irradiation, the number density and average diameter of loops increased significantly and more serious damage was caused under the synergistic effect of hydrogen and helium. The mechanism based on in-situ experimental observation was discussed in depth. Graphical Abstract: Graphical Abstract Image, graphical abstract .